2016
DOI: 10.1161/strokeaha.115.011867
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cells Lining Sporadic Cerebral Cavernous Malformation Cavernomas Undergo Endothelial-to-Mesenchymal Transition

Abstract: Our findings support the use of common therapeutic strategies for both sporadic and genetic CCM malformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 15 publications
3
48
0
Order By: Relevance
“…Loss-of-function of CCM proteins has also been shown to trigger β-catenin and transforming growth factor beta/bone morphogenetic protein (TGFβ/BMP) signaling-driven endothelial-to-mesenchymal transition (EndMT) (Bravi et al, 2016, Bravi et al, 2015, Guan and Couldwell, 2013, Maddaluno et al, 2013), as well as activation of MEKK3 signaling and increased expression of the mechanosensitive transcription factors KLF2 and KLF4 (Cullere et al, 2015, Cuttano et al, 2016, Fisher et al, 2015; Zhou et al, 2015; Zhou et al, 2016). Both of these mechanisms have been suggested to be key determinants of CCM disease pathogenesis (Maddaluno et al, 2013, Bravi et al, 2016, Cuttano et al, 2016, Zhou et al, 2016).…”
Section: Current Knowledge Of the Molecular Basis And Mechanisms Of Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Loss-of-function of CCM proteins has also been shown to trigger β-catenin and transforming growth factor beta/bone morphogenetic protein (TGFβ/BMP) signaling-driven endothelial-to-mesenchymal transition (EndMT) (Bravi et al, 2016, Bravi et al, 2015, Guan and Couldwell, 2013, Maddaluno et al, 2013), as well as activation of MEKK3 signaling and increased expression of the mechanosensitive transcription factors KLF2 and KLF4 (Cullere et al, 2015, Cuttano et al, 2016, Fisher et al, 2015; Zhou et al, 2015; Zhou et al, 2016). Both of these mechanisms have been suggested to be key determinants of CCM disease pathogenesis (Maddaluno et al, 2013, Bravi et al, 2016, Cuttano et al, 2016, Zhou et al, 2016).…”
Section: Current Knowledge Of the Molecular Basis And Mechanisms Of Cmentioning
confidence: 99%
“…Both of these mechanisms have been suggested to be key determinants of CCM disease pathogenesis (Maddaluno et al, 2013, Bravi et al, 2016, Cuttano et al, 2016, Zhou et al, 2016). Moreover, it has been also suggested that increased Rho activity, as well as proteolytic activity of extracellular matrix metalloprotease ADAMTS, arises secondary to increased MEKK3–KLF2/4 signaling during CCM formation (Zhou et al, 2016).…”
Section: Current Knowledge Of the Molecular Basis And Mechanisms Of Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Bravi et al also found that once this change occurred in the endothelial cells of CCMs, TGF-β/BMP signaling was subsequently required for the progression of the disease (48). The authors also found that this endothelial-to-mesenchymal cell transformation occurred in sporadic CCM lesions in addition to the familial and animal model lesions (49). While these findings are interesting from a pathogenic standpoint, they are even more intriguing because they suggest potential therapeutic options for the treatment and prevention of CCMs.…”
Section: Additional Developmentsmentioning
confidence: 83%
“…Of all these bona fide interactors, MEKK3 [92, 93, 101-104], has emerged as a key player in the formation and progression of CCM lesions. Gain of MEKK3 signaling and upregulation of its targets, the transcription factors KLF2 and KLF4 have been causally linked to CCM pathogenesis and onset and progression of lesions [105-107], preceding endothelial-to-mesenchymal transition, underlain by changes in TGF-β/BMP signaling sensitivity [82, 108, 109]. Additional work will be needed to fully elucidate lesion formation at the cellular and molecular level.…”
Section: Hereditary Hemorrhagic Cerebrovascular Diseasementioning
confidence: 99%